Proposal of MUAC as a fast tool to monitor pregnancy nutritional status: Results from a cohort study in Brazil - Miele, Maria J.; Souza, Renato T.; Calderon, I. M.P. [UNESP]; Feitosa, Francisco; Leite, Debora F.; Rocha Filho, Edilberto; Vettorazzi, Janete; Mayrink, Jussara; Fernandes, Karayna G.; Vieira, Matias C.; Pacagnella, Rodolfo C.; Cecatti, Jose Guilherme (BMJ, 2021)
Objective In Brazil, although the assessment of maternal nutritional status is recommended using body mass index (BMI), this is only possible in settings adequately prepared. Midupper arm circumference (MUAC) is another biological variable identified as a tool for rapid assessment of nutritional status that is correlated with BMI. Therefore, we aim to surrogate BMI by MUAC cut-offs for rapid screening of maternal nutritional status starting at midpregnancy. Design Analysis of the multicentre cohort study entitled 'Preterm SAMBA' using an approach of validation of diagnostic test. Setting Outpatient prenatal care clinics from five tertiary maternity hospitals from three different Brazilian regions. Participants 1165 pregnant women attending prenatal care services from 2015 to 2018 and with diverse ethnic characteristics who were enrolled at midpregnancy and followed in three visits at different gestational weeks. Primary and secondary outcome measures Sensitivity, specificity, positive and negative predictive values, likelihood ratio and accuracy of MUAC being used instead of BMI for the assessment of nutritional status of women during pregnancy. Results We found a strong correlation between MUAC and BMI, in the three set points analysed (r=0.872, 0.870 and 0.831, respectively). Based on BMI categories of nutritional status, we estimated the best MUAC cut-off points, finding measures according to each category: Underweight <25.75 cm (19-39 weeks); overweight 28.11-30.15 cm (19-21 weeks), 28.71-30.60 cm (27-29 weeks) and 29.46-30.25 cm (37-39 weeks); and obese >30.15 cm (19-21 weeks), >30.60 cm (27-29 weeks) and >30.25 cm (37-39 weeks) per gestational week. Therefore, we defined as adequate between 25.75-28.10 cm (19-21 weeks), 25.75-28.70 cm (27-29 weeks) and 25.75-29.45 cm (37-39 weeks) of MUAC. Conclusion We conclude that MUAC can be useful as a surrogate for BMI as a faster screening of nutritional status in pregnant women.
Keywords: maternal medicine; nutrition & dietetics; prenatal diagnosis